2018
DOI: 10.1080/19396368.2018.1504347
|View full text |Cite
|
Sign up to set email alerts
|

Making IVF more effective through the evolution of prediction models: is prognosis the missing piece of the puzzle?

Abstract: IVF: In vitro fertilization; ART: assisted reproduction techniques; BMI: body mass index; OHSS: ovarian hyperstimulation syndrome; eSET: elective single embryo transfer; ESHRE: European Society of Human Reproduction and Embryology; mtDNA: mitochondrial DNA; nDNA: nuclear DNA; ICSI: intracytoplasmic sperm injection; MBR: multiple birth rates; LBR: live birth rates; SART: Society for Assisted Reproductive Technology Clinic Outcome Reporting System; AFC: antral follicle count; GnRH: gonadotrophin releasing hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…It would be interesting, however, to combine several parameters to build an algorithm that could predict the outcome of IVF treatment, e.g. to combine caspase-3 levels in the secretome with detailed studies of embryo development (as in the study by Dominguez), in combination with age, BMI and possible biological markers studied in other investigations (reviewed in [47]).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting, however, to combine several parameters to build an algorithm that could predict the outcome of IVF treatment, e.g. to combine caspase-3 levels in the secretome with detailed studies of embryo development (as in the study by Dominguez), in combination with age, BMI and possible biological markers studied in other investigations (reviewed in [47]).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of AMH in the blood of cows subjected to superovulatory treatment were used as a marker to predict ovarian responses and consequently the quality of recovered embryos [14,18,23,24]. The study herein showed that, the correlations between AMH concentrations and ovarian response were significant positive (P<0.05) for CL (r=0.36), total ovarian response (P<0.01; r=0.80), transferable embryos (r=0.32), and freezable embryos (r=0.35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antral follicle count and AMH level are contributed to these variability's [12,13]. Selection of candidate donor's cows for embryos production based on AMH level will reduce this variability [14]. AMH secreted by the granulosa cells of the ovary and characteristic for each animal on a long term period [15] and providing highly accurate information on the ovarian follicular pool and follicular responsiveness [16].…”
Section: Introductionmentioning
confidence: 99%
“…Decades after the first successful application of ART in humans, over 8 million infants have been born with ART assistance worldwide ( Wade et al, 2015 ; Rao et al, 2018 ; Fauser, 2019 ; Leaver and Wells, 2019 ). ART has become well-accepted and popular in recent years ( Liu et al, 2015 ; Simopoulou et al, 2018 ; Gleicher et al, 2019 ). Epidemiological and animal experiments show that the early stage of fetal development is particularly sensitive to changes in the environment and that the environmental abnormalities suffered during this period may lead to problems later in life ( Faulk and Dolinoy, 2011 ; Hanson and Gluckman, 2014 ; Grandjean et al, 2015 ; Heindel et al, 2017 ; Li T. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%